The effect of follicular fluid hormones on oocyte recovery after ovarian stimulation: FSH level predicts oocyte recovery - Rinaudo Paolo F; McCulloch Charles E; Dobson Anthony T; Shen Shehua; Zamah A Musa; Rosen Mitchell P; Lamb Julie D; Cedars Marcelle I (BMC, 2009)
Abstract Background Ovarian stimulation for assisted reproductive technology (ART) overcomes the physiologic process to develop a single dominant follicle. However, following stimulation, egg recovery rates are not 100%. The objective of this study is to determine if the follicular fluid hormonal environment is associated with oocyte recovery. Methods This is a prospective study involving patients undergoing ART by standard ovarian stimulation protocols at an urban academic medical center. A total of 143 follicular fluid aspirates were collected from 80 patients. Concentrations of FSH, hCG, estradiol, progesterone, testosterone and prolactin were determined. A multivariable regression analysis was used to investigate the relationship between the follicular fluid hormones and oocyte recovery. Results Intrafollicular FSH was significantly associated with oocyte recovery after adjustment for hCG (Adjusted odds ratio (AOR) = 1.21, 95%CI 1.03-1.42). The hCG concentration alone, in the range tested, did not impact the odds of oocyte recovery (AOR = 0.99, 95%CI 0.93-1.07). Estradiol was significantly associated with oocyte recovery (AOR = 0.98, 95% CI 0.96-0.99). After adjustment for progesterone, the strength of association between FSH and oocyte recovery increased (AOR = 1.84, 95%CI 1.45-2.34). Conclusion The relationship between FSH and oocyte recovery is significant and appears to work through mechanisms independent of the sex hormones. FSH may be important for the physiologic event of separation of the cumulus-oocyte complex from the follicle wall, thereby influencing oocyte recovery. Current methods for inducing the final stages of oocyte maturation, with hCG administration alone, may not be optimal. Modifications of treatment protocols utilizing additional FSH may enhance oocyte recovery.